Effect of L-thyroxine on left ventricular function in subclinical hypothyroidism - Nakova, Valentina Velkoska; Krstevska, Brankica; Srbinovska Kostovska, Elizabeta; Pemovska, Gordana (Bioscientifica, 2015)
Introduction: Thyroid hormone deficiency can lead to the impairment of cardiac function. Whether subclinical hypothyroidism (ScH) is a risk factor for left ventricular (LV) dysfunction is controversial. Aim of the study was to assess whether ScH is associated with LV systolic and diastolic dysfunction and it’s reversibility after treatment with L-thyroxine. Material and methods: Twenty-seven consecutive patients with newly diagnosed ScH underwent laboratory analyses (TSH, fT4, fT3, anti-TPO, and anti-Tg antibodies), and a complete two-dimensional echocardiography study. Results: Analysed patients has the following characteristics: age 41±12 years, TSH 8.5±2.7 mU/l before treatment, and TSH 2.07±0.9 mU/l after an average follow-up period of 7.2±1.9 months. Compared to baseline measurements, after 5 months euthyroid stage the duration of the A wave was shorter (112.18±17.2 ms vs 112.18±17.2 ms, P<0.01), and the longitudinal global strain was higher (−19.55±2.3% vs −20.07±2.7%, P<0.05). Free T4 positively correlated with E/A ratio (r=0.42, P<0.05) and fT3 negatively correlated with DT (r=−0.50, P<0.05). Univariant regression analysis showed a statistically significant independent effect of TSH on the E/e’ lat, E/e’ average, LVED vol, LA, and LA area. Conclusion: Subclinical hypothyroidism is associated with systolic and diastolic LV dysfunction, as well as reducing global longitudinal LV systolic function. These alterations may be reversed by L-thyroxine.